An analysis of the methods and materials for 4-dimensional printing. (2021) - Manikandan, N.; Rajesh, P.K.; Harish, V.
Abstract: The introduction of Additive Manufacturing (AM) in the late 1980s has transformed the manufacturing industry and even reached the desks of hobbyists. AM is a manufacturing technique in which a prototype is produced by the deposition of a material progressing one layer at a time. This technology has several drawbacks in spite of continuous research and improvements. Issues such as speed of printing, surface finish of the final product and lack of fully functional materials still needs addressing. A new kind of printing referred as 4-dimensional (4D) printing has recently been introduced. 4D printing is the additive manufacturing of smart materials in which the 3D printed shapes exhibit shape change behavior. The stimuli responsive materials, the stimuli and the time taken for the state change to occur constitute key research areas in 4D printing. This study summarizes the developments in 4D printing technology with emphasize on the materials and methods used for the fabrication of 4D printed structures. It was found that the common processes for the fabrication of smart structure are Stereolithography, Fused Filament Fabrication, Digital Light Projection, Inkjet printing, Selective Laser Melting and Direct Ink Writing. The printed smart structures can be triggered with external stimuli such as water, heat, electricity, light and solvents with different pH values. Even though the printed structures show self-healing and self-diagnosis capabilities; self-actuation and self-sensing are still under research. In order to make this technology sustainable for the future, issues such as standardization of the printing process and the interaction mechanism between the material and process still needs addressing.